Criminal Case of Forgery Under Article 263 of the Criminal Code Regarding Jokowi’s Diploma Dismissed by BARESKRIM Due to Potential Misuse in Criminal Procedural Practice - Panggabean, Tardip (Indonesia of Journal Business Law, 2025)
This study analyzes the termination of the criminal investigation concerning the alleged forgery of President Joko Widodo's diploma, under Article 263 of the Indonesian Criminal Code. Despite strong public attention and legal accusations filed by civil society group TPUA, Bareskrim Polri concluded there was no criminal offense and ceased the case. The research highlights the legal framework for case termination via SP3 (Investigation Termination Order) and discusses potential procedural misuses in the investigation phase. It further evaluates the forensic analysis conducted on Jokowi’s academic documents and legal remedies available for objecting to termination decisions. Using a normative juridical approach, this study finds significant procedural ambiguity and the potential for institutional overreach in preliminary inquiries. The case study demonstrates the challenges in maintaining legal accountability and transparency when criminal allegations involve high-profile political figures. Recommendations are made for reforming the criminal procedural mechanisms to uphold justice and public trust. This raises concern over potential misuse of investigative mechanisms, with what amounts to an SP3 (Order to Terminate Investigation) being issued under a different guise. As such, the case may rightfully become the subject of a pretrial motion (pretrial) to assess its legal validity. Although many criminal cases never proceed to the investigation stage, they typically do not involve public figures as prominent as those in this alleged fake diploma case. Therefore, they often do not go viral or receive widespread media coverage in print or electronic news, unlike the ongoing attention this case has attracted.